2001
DOI: 10.1258/0022215011908955
|View full text |Cite
|
Sign up to set email alerts
|

Significance of human papillomavirus in sinonasal papillomas

Abstract: Recent investigations have suggested human papillomavirus (HPV) to be involved in the development of sinonasal papillomas (SNP). Forty-three patients operated for SNP were studied to determine the prevalence of HPV-DNA sequences in these tumours and to evaluate their value as a prognostic parameter. The original sections of all cases were reviewed and reclassified according to the WHO. Paraffin blocks available from 37 patients were subjected to in situ hybridization (ISH) and polymerase chain reaction (PCR). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
1
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 12 publications
0
41
1
4
Order By: Relevance
“…Nineteen of 20 HPV-positive IPs in our study showed HPV-11, and one showed HPV-6. These data were compared with the results of 22 published studies in which PCR was used for HPV detection [15,22,23,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. As summarized in Table 2, a total of 720 IPs have been analyzed in previous studies, and HPV DNA was detected in 203 (28.1%).…”
Section: Discussionmentioning
confidence: 99%
“…Nineteen of 20 HPV-positive IPs in our study showed HPV-11, and one showed HPV-6. These data were compared with the results of 22 published studies in which PCR was used for HPV detection [15,22,23,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. As summarized in Table 2, a total of 720 IPs have been analyzed in previous studies, and HPV DNA was detected in 203 (28.1%).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple infections were separated into constituent types; thus, type-specific detection represents types found alone or with other HPV types. Consensus PCR primers MY09/11, PGMY09/11, GP5+/6+, and SPF10 were considered to amplify the 18 HPV types most commonly associated with cervical and head and neck cancers (6,11,16,18,31,33,35,39,45,51,52,56,58,59,66,68,70,73,82, and 83) as well as additional high-and low-risk types. It is important to note that an HPV type was only considered tested for if it was, a) amplified by the primers and subsequently genotyped in analyses using PCR-based methods, or b) probed for using sequences specific to those types in the DNAbased (SB) and RNA-based (ISH) analyses.…”
Section: Data Abstractionmentioning
confidence: 99%
“…Low-risk/highrisk coinfections are rare and found in three studies [2,9,29]. Several studies also specifically tested for HPV 31/33/ 35 [12, 16, 20-22, 24, 28, 31] as well as HPV 42-45, 51, 52, 56, 58 [1,22,24,31] with negative results. Ogura [1] found HPV 57 in 1 of 3 cases and Wu [8] detected 57b in 9 of 15 IP studied; however this could not be confirmed by others [30].…”
Section: Hpv Types Distribution In Inverted Papillomasmentioning
confidence: 99%
“…Hicks W Jr et al [12] and Schwerer MJ et al [28] evaluated the expression patterns of cytokeratins in nasal polyps and IP, The columnar differentiation cytokeratins (ex: CK 7,8,18,19,20) were positive in both NPs and IPs but the squamous differentiation cytokeratins (ex: CK 10,10/13, 1/ 2/10/11) were positive in IP but not in NP. For both group of cases the immature cell type CKs were positive at the basal layer.…”
Section: Patterns Of Cytokeratin Expressionmentioning
confidence: 99%
“…HPV is evaluated both for IP and nasal polyps but not for REAH [9,13,19]. Kraft et al [19] identified HPV11 in only 1(3%) out of 29 IP cases, while HPV 6b, 16 and 18 were negative by in situ hybridization. Hoffman M et al [13] detected HPV DNA type 6 and 11 in 3 of 26 cases, while 20 nasal polyps were negative.…”
Section: Association With Virusesmentioning
confidence: 99%